Seasonal abundance of the demersal copepod Pseudodiaptomus cokeri (Calanoidea: Pseudodiaptomidae) in a Caribbean estuarine environment - Ríos Jara, Eduardo (Universidad de Costa Rica, 1998)
Seasonal abundance variations of the demersal copepod Pseudodiaptomus cokeri were examinated at three locations (center, north shore and south shore) in Phosphorescent Bay, Puerto Rico, throughout an annual cycle. Nocturnal oblique tows ( 2 1 :00-2 3 :00 hr) were taken biweeldy (three replicates) at each location with a coDicaI net (mouth diamcter = 0.5 m; mesh size = 1 35 11m) and a standard calibrated flowmeter. Water temperature and salinity measurements were taken at the surface and near the bottom in each location before towing activities using a SCT meter. o Chlorophyll-a concentrations were fluorometricaIly determined. The adult and copepodite stages of this species accountcld for approximately 1 .6% of the annual mean total zooplankton abundance of the bayo Higher abundance of P. cokeri (mean:l:l SD = 4 1 9 1 :!: 1 444 iÍldividuals m-3) was associated with ool water temperatures and dry conditions (cooVdry season) which prevailed betw'een December and March relative to the period between April and November (wann/wet seasón) with lower abundance. F1uctuations of this population followed progressive increments in chlorophyll- a concentrations at the three sampling statigns (One-way ANOVA)